Quantitative confocal laser scanning microscopy - Krog-Raarup, Merete (Image analysis and stereology, 2006)
This paper discusses recent advances in confocal laser scanning microscopy (CLSM) for imaging of 3D structure as well as quantitative characterization ofbiomolecular interactions and diffusion behaviour by means of one- and two-photon excitation. The use of CLSM for improved stereological length estimation in thick (up to 0.5 mm) tissue is proposed. The techniques of FRET (Fluorescence Resonance Energy Transfer), FLIM (Fluorescence Lifetime Imaging Microscopy), FCS (Fluorescence Correlation Spectroscopy) and FRAP (Fluorescence Recovery After Photobleaching) are introduced and their applicability for quantitative imaging of biomolecular (co-)localization and trafficking in live cells described. The advantage of two-photon versus one-photon excitation in relation to these techniques is discussed.
Keywords: Microscopy, Confocal; Mikroskopija konfokalna; Slika, obdelava z računalnikom; Image Processing, Computer-Assisted; mikroskopija; laserski mikroskop; stereologija